Conjugal and cohabitation agreements and the preliminary draft of the Civil Code review (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2024)
The article analyzes the expansion of contractual freedom in conjugal and cohabitation relationships, addressing the need to break with the discourse against the contractualization of patrimonial effects. It discusses the proposals of the preliminary draft of the Civil Code reform, which aim to expand the autonomy of the parties and provide greater predictability to patrimonial effects, without neglecting the protection against economic and social imbalances in the relationships.Received in: August 2024 | Accepted in: October 2024
Keywords: Agreements; Contractual freedom; Civil Code